Erosion Hazard Analysis Using the RUSLE Model in the Upper Opak Sub Watershed: Analisis Bahaya Erosi Menggunakan Model RUSLE di Daerah Aliran Sungai Opak Hulu - Priyono, Hendro; Munawar, Ali (Jurnal Ilmu Tanah dan Air, 2025)
The increase of population causes changes in land use patterns that are not always suitable with conservation rules. This condition makes erosion risk higher, especially in the upstream area of Opak Sub-watershed, which has an important role to keep hydrological function from upstream to downstream. This research aims to analyze the erosion hazard level in the upstream part of Opak Sub-watershed by using the Revised Universal Soil Loss Equation (RUSLE) model with Geographic Information System (GIS) and remote sensing data. The R factor was calculated from 10 years of rainfall data, the K factor was obtained from physical and chemical analysis of 10 soil samples, the LS factor was calculated from DEMNAS image, while the C and P factors were taken from Sentinel-2A image using supervised classification with Maximum Likelihood method and MSAVI vegetation index analysis. The result shows that erosion rate is between 0 and 163.892 tons/ha/year. From the total area of 6.785,33 ha, about 2.585,08 ha (38,10%) is in the Very Severe erosion hazard category (>480 tons/ha/year). In general, 92,43% of the total area in the upstream of Opak Sub-watershed has erosion rate above the allowed limit (Tm = 10,89 tons/ha/year), which means that comprehensive conservation actions are needed. Keywords: erosion, RUSLE, watershed